The role of bacterial outer membrane vesicles in inflammatory response of acute-on-chronic liver failure - Xiaojing Qin; Shuang Wang; Zhanyao Yan; Ninghui Zhao; Jia Yao (Frontiers in Microbiology, 2025)
Acute-on-chronic liver failure (ACLF) is a clinical syndrome that manifests as acute deterioration of liver function due to a series of etiologies and triggers in patients with pre-existing chronic liver diseases. Systemic inflammatory response is the major feature of ACLF. Gut microbiota dysbiosis impairs the intestinal barrier, facilitating the translocation of microorganisms and their metabolites into the liver and thereby exacerbating liver inflammation and disease progression. Recent studies have revealed that bacterial outer membrane vesicles (OMVs) derived from gut microbiota act as key mediators in microbiota-host cell communication. This article elucidates the possible roles of OMVs in ACLF inflammation and their underlying mechanisms.